An Alternative Geometry for Quantum Cellular Automata. Issue 1 (1998) - Krause, Paul G.; Mueller, Rachel M.; Tougaw, P. Douglas; Weidner, Janelle M.
Abstract : We examine an alternative layout geometry for the quantum cellular automata (QCA) architecture. In the traditional QCA geometry, all of the cells are placed in a single plane, so that each cell interacts with a particular neighbor only along one of its edges. By rotating the cells out of the plane, we make it possible for neighbors to interact along all four edges at once. This increased interaction leads to a more bistable cell-cell response function and a 50% higher excitation energy. We also present a majority logic gate designed using three-dimensional cells.